Reliability improvement in Hallux Valgus measurement using weight-Bearing CT scan - Prusmetikul S. (2023)
Background: Radiographic assessment of hallux valgus is an essential process. Residual rotational deformity was shown associated with higher recurrent rate. This study aims to comprehensively assess reliability of measurement of various parameters from plain films and weight-bearing CT scan. Methods: A total of 40 pre-operative plain radiographs, 40 post-operative plain radiographs, and 37 weight-bearing CT scan were evaluated to determine reliability of hallux valgus parameters. Results: TSP and head shape representing coronal plane deformity showed lower inter-observer reliability compared to other parameters using for transverse plane evaluation especially in post-operative period. (post-op TSP amongst 3 assessors: κ = 0.386, 0.520, 0.340; post-op head shape: κ = 0.374, 0.375, 0.295) Using α angle for evaluation 1st metatarsal rotation in weight-bearing CT scan demonstrated very good reliability for inter-observer (ICC = 0.853 (95% CI = 0.715–0.925)) and intra-observer (ICC = 0.902 (95% CI = 0.844–0.939)). Conclusion: Weight-bearing CT scan can improve reliability in post-operative coronal plane assessment.